2014
DOI: 10.1245/s10434-014-4242-0
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of PRRX1 Confers Cancer Stem Cell-Like Properties and Predicts Poor Prognosis in Hepatocellular Carcinoma

Abstract: Downregulation of PRRX1 expression contributes to the poor prognosis of patients with HCC through acquisition of CSC-like properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 21 publications
3
31
0
Order By: Relevance
“…In agreement, FD-conditioned HCC (Mahlavu and SK-Hep1), glioblastoma multiforme (U87MG) and lung cancer (H441) cells showed a significant increase in self-renewal ability as evident by the increased number of spheres formed and expression level of stemness associated markers such as Oct4, β-catenin and the percentage of CD133-positive cells. A recent study demonstrated that downregulation of paired related homeobox 1 (PRRX1) is associated with the acquisition of cancer stem cell (CSC)-like properties and poor prognosis in HCC patients [38]. In agreement, we also found that PRRX1 was down-regulated in the HCC spheres generated under FD condition.…”
Section: Discussionsupporting
confidence: 86%
“…In agreement, FD-conditioned HCC (Mahlavu and SK-Hep1), glioblastoma multiforme (U87MG) and lung cancer (H441) cells showed a significant increase in self-renewal ability as evident by the increased number of spheres formed and expression level of stemness associated markers such as Oct4, β-catenin and the percentage of CD133-positive cells. A recent study demonstrated that downregulation of paired related homeobox 1 (PRRX1) is associated with the acquisition of cancer stem cell (CSC)-like properties and poor prognosis in HCC patients [38]. In agreement, we also found that PRRX1 was down-regulated in the HCC spheres generated under FD condition.…”
Section: Discussionsupporting
confidence: 86%
“…Paired-related homeobox 1 (PRRX1) was recently identified as a new EMT inducer (11). Furthermore, aberrant expression of PRRX1 is significantly associated with poor prognosis in various solid tumors including breast (11), colorectal (12), gastric cancer (13) and HCC (14). High PRRX1 expression levels were significantly associated with reduced metastasis and good prognosis in breast cancer (11), but the opposite relationship was observed in colorectal cancer and gastric cancer (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…High PRRX1 expression levels were significantly associated with reduced metastasis and good prognosis in breast cancer (11), but the opposite relationship was observed in colorectal cancer and gastric cancer (12,13). Downregulation of PRRX1 expression contributed to the poor prognosis of patients with breast cancer and HCC through acquisition of CSC-like properties (11,14). However, the direct mechanisms through which PRRX1 regulates HCC cells is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…CD13, which helps pause LCSCs in G1/G0 phase of the cell cycle [25], has already proven a useful drug target: the combination of a CD13 inhibitor with the genotoxin fluorouracil (5-FU) led to significantly smaller tumor size than either drug on its own in a mouse xenograft tumor model [26]. CD13 is special among LCSC markers because its level changes during differentiation of LCSCs in culture [36]: upregulation of CD13 is associated with the epithelial-mesenchymal transition and with a reduction in apoptosis.…”
Section: Discussionmentioning
confidence: 99%